Factors associated with work-related neck, shoulder and low back pain among rubber tappers at felda settlement in Jempol, Negeri Sembilan, Malaysia - Chow, Li Shan (2010)
A cross-sectional study among rubber tappers was conducted to determine the association between risk factors namely personal characteristics, ergonomic and psychosocial factors with work-related musculoskeletal symptoms (WMSS). Simple random sampling method was adopted and total of 419 rubber workers in each FELDA’s scheme at Jempol, Negeri Sembilan participated in this study. Data was collected through face to face interview using Standardized Nordic Questionnaire (SNQ) and Job Content Questionnaire (JCQ). The results revealed prevalence of WMSS according to anatomical body region was the highest for neck pain (59.9%) followed by low back pain (56.3%) and shoulders pain (54.9%). Risk factors of occupational stress revealed that these workers had low level of social support (71.4%), psychological demand (65.6%), job dissatisfaction (64.2%), decision latitudes (56.3%), depression (53.7%) and job insecurity (52.5%). There were 13 risk factors found to be significantly related to WMSS, age, working hours per day, job insecurity, depression, repetitive motion, heavy lifting, twisting and bending, manual handling materials, static posture, awkward posture, harmful standing, neck flexion or rotation and vibration with p<0.05 revealed significant association with WMSS. Multivariate analyses were focused on neck, shoulder and low back pain. Multivariate logistic analysis showed risk factors for neck pain (NP) were decreased with age (OR= 3.92, 95% CI 1.61 – 9.58), increase in neck flexion or rotation (OR= 9.52, 95% CI 5.55 – 16.32), awkward postures (OR=2.23, 95% CI 1.29 – 3.86) and static postures (OR=1.86, 95% CI 1.10 – 3.14). Low back pain (LBP) was associated with number of trees tapped per day with less than 100 trees (OR= 4.45, 95% CI 1.38 – 14.39) and 100 to 300 trees (OR= 3.55, 95% CI 1.19 – 10.59), heavy lifting (OR= 2.27, 95% CI 1.37 – 3.77), twisting and bending (OR= 3.32, 95% CI 2.03 - 5.45) and vibration (OR= 2.02, 95% CI 1.21 – 3.37). Age in 49 to 58 years old (OR=2.12, 95% CI 1.03 – 4.37), ethnic (OR= 0.23, 95% CI 0.06 – 0.90), manual handling materials (OR= 3.21, 95% CI 1.93 – 5.35), awkward postures (OR= 2.77, 95% CI 1.60 – 4.93), neck flexion or rotation (OR= 2.11, 95% CI 1.23 – 3.62), repetitive motion (OR= 1.80, 95% CI 1.02 – 3.19) and heavy lifting (OR= 1.83, 95% CI 1.07 – 3.11) were also significant factors in shoulder pain (SP). The high prevalence of WMSS is a significant problem among rubber tappers and it’s associated with various occupational risk factors. This finding showed that management should instituted health promotion and awareness program to curb this problem.